Continuity and Discontinuity in Cultural Conditioning Ruth Benedict - M. Refki Yansyah (PT. Anagata Sembagi Education, 2024)
In our culture, the human growth cycle is a constant, from vulnerable infants to adults. Ruth Benedict underscores the physiological contrast between the two, as well as the roles that change over time. While these facts of nature underlie discussions of humans, the anthropologist's role is to analyze the interaction between